Objective but not subjective sleep predicts memory in community‐dwelling older adults. (12th February 2016) - Cavuoto, Marina G.; Ong, Ben; Pike, Kerryn E.; Nicholas, Christian L.; Bei, Bei; Kinsella, Glynda J.
Summary: Research on the relationship between habitual sleep patterns and memory performance in older adults is limited. No previous study has used objective and subjective memory measures in a large, older‐aged sample to examine the association between sleep and various domains of memory. The aim of this study was to examine the association between objective and subjective measures of sleep with memory performance in older adults, controlling for the effects of potential confounds. One‐hundred and seventy‐three community‐dwelling older adults aged 65–89 years in Victoria, Australia completed the study. Objective sleep quality and length were ascertained using the Actiwatch 2 Mini‐Mitter, while subjective sleep was measured using the Pittsburgh Sleep Quality Index. Memory was indexed by tests of retrospective memory (Hopkins Verbal Learning Test – Revised), working memory (n‐back, 2‐back accuracy) and prospective memory (a habitual button pressing task). Compared with normative data, overall performance on retrospective memory function was within the average range. Hierarchical regression was used to determine whether objective or subjective measures of sleep predicted memory performances after controlling for demographics, health and mood. After controlling for confounds, actigraphic sleep indices (greater wake after sleep onset, longer sleep‐onset latency and longer total sleep time) predicted poorer retrospective (∆ R 2   = 0.05, P  = 0.016) and working memory (∆ R 2   = 0.05, P  = 0.047). In contrast, subjective sleep indices did not significantly predict memory performances. In community‐based older adults, objectively‐measured, habitual sleep indices predict poorer memory performances. It will be important to follow the sample longitudinally to determine trajectories of change over time.